Effect of Spinal Cord Compression on Local Vascular Blood Flow and Perfusion Capacity - Alshareef, Mohammed (Public Library of Science, 2014)
Spinal cord injury (SCI) can induce prolonged spinal cord compression that may result in a reduction of local tissue perfusion, progressive ischemia, and potentially irreversible tissue necrosis. Due to the combination of risk factors and the varied presentation of symptoms, the appropriate method and time course for clinical intervention following SCI are not always evident. In this study, a three-dimensional finite element fluid-structure interaction model of the cervical spinal cord was developed to examine how traditionally sub-clinical compressive mechanical loads impact spinal arterial blood flow. The spinal cord and surrounding dura mater were modeled as linear elastic, isotropic, and incompressible solids, while blood was modeled as a single-phased, incompressible Newtonian fluid. Simulation results indicate that anterior, posterior, and anteroposterior compressions of the cervical spinal cord have significantly different ischemic potentials, with prediction that the posterior component of loading elevates patient risk due to the concomitant reduction of blood flow in the arterial branches. Conversely, anterior loading compromises flow through the anterior spinal artery but minimally impacts branch flow rates. The findings of this study provide novel insight into how sub-clinical spinal cord compression could give rise to certain disease states, and suggest a need to monitor spinal artery perfusion following even mild compressive loading.